2021
DOI: 10.1016/j.jns.2021.117554
|View full text |Cite
|
Sign up to set email alerts
|

Potentials to alleviate coagulopathy and enhance microglial function of beta (β)- glucans, making them worth a clinical study for COVID-19's neurological sequalae

Abstract: Widespread neurological and psychiatric sequalae of COVID-19 have been reported affecting all age groups [1] with presence of low-grade chronic inflammation and down-regulated ACE-2 levels making the individual more vulnerable for severe neurological effects of COVID-19 [2] as there will be greater disruption of the blood-brain barrier and hyper inflammation. Systemic immune inflammation index (SII) including neutrophil, platelet and lymphocyte counts serve as potential biomarkers to find an individual's risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…-Glucan is used classically to boost the immune system and to treat hyper chole sterolemia [7,12,13,14]. For example, -glucan can modulate the autoimmune mechanisms directed to pancreatic islets and inhibit the development of diabetes mellitus [15,16]. It is of interest that in the central nervous system, -glucans activate microglial cells, which act as scavengers of the brain cell debris and play a protective role in Alzheimer's disease, AIDS, ischemia injury, and multiple sclerosis [5,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…-Glucan is used classically to boost the immune system and to treat hyper chole sterolemia [7,12,13,14]. For example, -glucan can modulate the autoimmune mechanisms directed to pancreatic islets and inhibit the development of diabetes mellitus [15,16]. It is of interest that in the central nervous system, -glucans activate microglial cells, which act as scavengers of the brain cell debris and play a protective role in Alzheimer's disease, AIDS, ischemia injury, and multiple sclerosis [5,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated the potential of β-glucans in the prevention, treatment, and complications of COVID-19 [14,169,170,[179][180][181][182][183][184][185][186][187][188][189][190][191][192]. Immunomodulatory, antioxidant, neuroprotective, and antithrombotic activities are of particular interest here.…”
Section: Discussionmentioning
confidence: 97%
“…In a follow-up analysis of this study, we have reported a significant decrease in Enterobacter and E. coli 25 which logically will result in lesser production of alpha-synuclein. In spite of such decreased production, the increase in plasma alpha-synuclein levels can be probably due to the disintegration of the amyloid deposits by natural killer cells leading to these alpha-synuclein entering the blood stream 26 27. These postulated mechanisms while need further in-depth research, no single intervention, or therapy has proven its ability to regulate alpha-synuclein levels, especially in children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…15 Beta-glucan has been proven to reduce the expression of inflammatory and proinflammatory markers, including Il-6 and TNF-α, 16 apart from having a neuroprotective effect by attenuating inflammatory cytokine production through microglia. 17 In another study, beta-glucan reduced induced microglia activation and its phagocytosis of synaptic puncta and upregulation of proinflammatory cytokine (TNF-α, IL-1β and IL-6) mRNA expression apart from promoting Tau signalling and improving cognition and brain function via the gutbrain axis. 18 This study was undertaken to investigate the effects of Nichi Glucan as a food supplement in children with ASD, especially with relevance to the Childhood Autism Rating Scale (CARS) score and alpha-synuclein levels.…”
Section: Open Accessmentioning
confidence: 97%
See 1 more Smart Citation